Pengaruh Corporate Governance Terhadap Struktur Modal Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2017 - Rahmi Aulia Putri; Yolandafitri Zulvia (Universitas Negeri Padang, 2019)
This study aims to examine the effect of corporate governance on the capital structure of manufacturing companies listed on the Indonesia Stock Exchange. Companies need an optimal capital structure so that there are no problems that will later impact the risk of high corporate bankruptcy. Capital structure will be optimal if there is no agency problem. Agency problems occur because of differences in interests between managers, investors, and creditors. To reduce agency conflict, corporate governance is needed. Institutional ownership and the size of the audit committee are used in this study as part of corporate governance. Debt to equity ratio was used to measure capital structure in this study. The sample used in this study amounted to 76 manufacturing companies listed on the Indonesia Stock Exchange. The sample selection in this study used a purposive sampling method. The type of data used is secondary data obtained from www.idx.co.id. The analytical method used is multiple regression analysis. The results of the study show that institutional ownership has a significant effect on capital structure, while the audit committee has no significant effect on capital structure. Keywords: capital structure, corporate governance, institusional ownership, audit committee